2022
DOI: 10.1186/s12905-022-01890-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of pelvic organ prolapse at public hospitals in Hawassa city, Southern Ethiopia, 2020: unmatched case control study

Abstract: Introduction Even though the Pelvic organ prolapse (POP) is outstanding gynecologic problem, most private and asymptomatic nature of the illness makes it the “hidden epidemic.” The aim of this study was to identify the determinants of POP. Methods Facility based unmatched case control study was conducted from June 15 to September 10, 2020. All cases diagnosed with POP were enrolled in the study by using consecutive random sampling method by assumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Similar to our ndings, studies from China and India have also shown the protective effect of education (39,40). For those who received less education, the chances of choosing light manual labor were greater, which was a certainly bene t to pelvic oor (41).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our ndings, studies from China and India have also shown the protective effect of education (39,40). For those who received less education, the chances of choosing light manual labor were greater, which was a certainly bene t to pelvic oor (41).…”
Section: Discussionsupporting
confidence: 89%
“…The effect of grand multiparty on POP was evaluated by using eight studies ( 13 , 20 , 21 , 28 , 31 , 39 , 43 , 44 ), and the result revealed that grand multiparty was significantly associated with POP. Grand multipara mothers were 5.42 times more likely to have POP than those primipara mothers (pooled odds ratio = 5.42, 95%CI = 4.06, 7.23).…”
Section: Resultsmentioning
confidence: 99%
“…It has a significant economic burden due to impaired daily activities and decreased productivity ( 10 ). The burden of POP is significantly higher in resource-limited countries because of the challenging socioeconomic and institutional factors ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicate that women with advanced POP in rural areas are more likely than those in urban areas to experience depression. This may be due to the sedentary lifestyles of rural residents and the physical demands of their jobs, as well as the fact that POP limits physical activity and worsens symptoms over time, which can lead to stress and depression [ 31 , 32 ]. This implies identifying, and early treatment will decrease the burden of depression in those who have risk factors for the development of POP [ 26 ].…”
Section: Discussionmentioning
confidence: 99%